Employ Frameworks and Modern Standards in Evaluating Internal Control System: Applied Research in the General Company for Vegetable Oil Industry (Journal of Accounting and Financial Studies ( JAFS ), 2019)
In light of today's business world, who faces challenges and intense competition as a result of the rapid evolution of technical and informational, organizations had to respond to variables through the adoption of modern management techniques that reduce the effects of risks and activating the role of the internal control system in order to contribute to the early detection of risks and reduce the negative results expected .The research is to address the problem faced by organizations which still follow the traditional methods in the control activities, and the lack of knowledge of the management and their staff of the importance of the existence of risk management and internal control system takes into account these risks, and the limiting of work of the internal auditors to detect irregularities, fraud, and routine control for operational activity . While that requires a mechanisms to activate the role of the internal control system to face the challenges through the internal auditors to give assurance on risk management processes, risk assessment being properly done, and evaluate the risk management processes. The research aims to establish a proposed framework for of internal control system according to the concept of enterprise risk management (ERM) with the recruitment of international ISO standards for the risk management in this context and proposed mechanism to evaluate the internal control system by the internal audit department